ADAPTATION OF FOREIGN STUDENTS TO TRAINING AT RUSSIAN UNIVERSITIES - Karen Amlaev; Stoyana Znamenskya; Natalia Mayatskaya (Вестник Северо-Кавказского федерального университета)
The article analyzes the problems of adaptation offoreign students to training at Russian universities; describes the characteristics and types of adaptation; the difficulties arising in the period of study of foreign students at Russian universities. The conditions for overcoming the psychological and educational barriers are determined. Methods of the student's adaptation to the socio-cultural environment, contributing to the early integration in the learning process are designated. In general, it should be noted the high level of adaptation of foreign students StGMU to the educational environment of the university.